2017
DOI: 10.1177/1932202x17730567
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Personality, Parenting Styles, and Perfectionism on Performance Goal Orientation in High Ability Students

Abstract: The current study explores relationships among gender, perceived parenting style, the personality traits of conscientiousness and neuroticism, perfectionism, and achievement goal orientation in a high ability and high achieving young adult population. Using data from Honors College students at a Midwestern university, a path model suggests that neuroticism and conscientiousness are positively related to self-oriented perfectionism, whereas neuroticism and authoritarian parenting style are positively related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 90 publications
1
26
1
10
Order By: Relevance
“…In addition to parental influence, personality traits have been found to relate to perfectionism among high-ability college students, which mirrors findings in the general population (Dunkley, Blankstein, & Berg, 2012; Hewitt & Flett, 1991). Miller and Speirs Neumeister (2017) examined a sample of 393 honors undergraduates and found the personality traits of conscientiousness and neuroticism had significant positive effects on self-oriented perfectionism (standardized regression weight = .465 and .310, p < .001, respectively). Neuroticism also had a positive effect on socially prescribed perfectionism (standardized regression weight = .280, p < .001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to parental influence, personality traits have been found to relate to perfectionism among high-ability college students, which mirrors findings in the general population (Dunkley, Blankstein, & Berg, 2012; Hewitt & Flett, 1991). Miller and Speirs Neumeister (2017) examined a sample of 393 honors undergraduates and found the personality traits of conscientiousness and neuroticism had significant positive effects on self-oriented perfectionism (standardized regression weight = .465 and .310, p < .001, respectively). Neuroticism also had a positive effect on socially prescribed perfectionism (standardized regression weight = .280, p < .001).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, no nonhonors comparison groups were included, leaving us unable to answer the question, “are honors students more perfectionistic that nonhonors students?” but we do have a stronger understanding of the way perfectionism may impact honors students. Both perceived parenting style (especially authoritarian) and personality (especially conscientiousness and neuroticism) were related to levels of reported perfectionism among honors students across a variety of studies (Miller et al, 2012; Miller & Speirs Neumeister, 2017; Speirs Neumeister, 2004a; Speirs Neumeister & Finch, 2006). Although we do not have nonhonors comparison groups to use to gauge prevalence of perfectionism, we can see that these findings related to parenting style and personality mirror the general population (Dunkley et al, 2012; Hewitt & Flett, 1991), which leaves us to wonder whether the notion of perfectionism among high-ability college students, either in prevalence or in experience, even differs from average-ability college students.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is extremely likely that honors college students have been identified as gifted at some point during their previous schooling. For instance, a study of 393 honors college students at one university found that nearly all Honors College students (92%) self-reported participation in gifted programming during elementary, middle, and/or high school, although the types of programs in which they had participated varied extensively (Miller & Speirs Neumeister, 2017).…”
Section: Characteristics Of Honors Colleges and Programsmentioning
confidence: 99%
“…La orientación a metas se refiere a los propósitos o razones de los estudiantes para guiar su comportamiento en situaciones académicas (Pintrich y Schunk, 2006). Existen múltiples propuestas en relación a la clasificación de las metas académicas (Elliot y McGregor, 2001;Miller y Speirs Neumeister, 2017). Sin embargo, podría decirse que un punto común entre todas ellas es que diferencian entre metas de aprendizaje o de dominio y metas de rendimiento.…”
Section: La Orientación a Metasunclassified